High vs. low tidal volume and pulmonary complications in patients with cervical spinal cord injury on mechanical ventilation: systematic review - Meregildo-Rodríguez, Edinson Dante; Vásquez-Tirado, Gustavo Adolfo; Quispe-Castañeda, Claudia Vanessa; del Carmen Cuadra-Campos, María; Contreras-Cabrera, Jhuliana M.; Pinedo-Portilla, Juan Luis (Frontiers in Medicine, 2024)
Cervical spinal cord injury (CSCI) patients on mechanical ventilation often lack standardized guidelines for optimal ventilatory support. This study reviews existing literature to compare outcomes between high tidal volume (HTV) and low tidal volume (LTV) strategies in this unique patient population. Methods: We searched for studies published up to August 30, 2023, in five databases, following a PECO/PICO strategy. We found six studies for quantitative analysis and meta-analyzed five studies. Results: This meta-analysis included 396 patients with CSCI and mechanical ventilation (MV), 119 patients treated with high tidal volume (HTV), and 277 with low tidal volume (LTV). This first meta-analysis incorporates the few studies that show contradictory findings. Our meta-analysis shows that there is no significant statistical difference in developing VAP between both comparison groups (HTV vs. LTV) (OR 0.46; 95% CI 0.13 -1.66; p > 0.05; I2: 0%), nor are there differences between the presence of other pulmonary complications when treating with HTV such as acute respiratory distress syndrome (ARDS), atelectasis, onset of weaning. Conclusions: In patients with CSCI in MV, the use of HTV does not carry a greater risk of pneumonia compared to LTV; in turn, it is shown as a safe ventilatory strategy as it does not establish an increase in other pulmonary complications such as ARDS, atelectasis, the onset of weaning nor others associated with volutrauma. It is necessary to evaluate the role of HTV ventilation in this group of patients in primary RCT-type studies.